Effects of Y361‐auto‐phosphorylation on structural plasticity of the HIPK2 kinase domain. (28th December 2017) - Scaglione, Antonella; Monteonofrio, Laura; Parisi, Giacomo; Cecchetti, Cristina; Siepi, Francesca; Rinaldo, Cinzia; Giorgi, Alessandra; Verzili, Daniela; Zamparelli, Carlotta; Savino, Carmelinda; Soddu, Silvia; Vallone, Beatrice; et al.
Abstract: The dual‐specificity activity of the homeodomain interacting protein kinase 2 (HIPK2) is regulated by cis ‐auto‐phosphorylation of tyrosine 361 (Y361) on the activation loop. Inhibition of this process or substitution of Y361 with nonphosphorylatable amino acid residues result in aberrant HIPK2 forms that show altered functionalities, pathological‐like cellular relocalization, and accumulation into cytoplasmic aggresomes. Here, we report an in vitro characterization of wild type HIPK2 kinase domain and of two mutants, one at the regulating Y361 (Y361F, mimicking a form of HIPK2 lacking Y361 phosphorylation) and another at the catalytic lysine 228 (K228A, inactivating the enzyme). Gel filtration and thermal denaturation analyzes along with equilibrium binding experiments and kinase assays performed in the presence or absence of ATP‐competitors were performed. The effects induced by mutations on overall stability, oligomerization and activity support the existence of different conformations of the kinase domain linked to Y361 phosphorylation. In addition, our in vitro data are consistent with both the cross‐talk between the catalytic site and the activation loop of HIPK2 and the aberrant activities and accumulation previously reported for the Y361 nonphosphorylated HIPK2 in mammalian cells.